Effectiveness of Learning Models Think Talk Write Assisted Canva app in Increase Critical Thinking and Collaboration Skills Elementary School Students - Arianti, Novi; Samsudin, Asep; Hutajulu, Masta (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The demands of 21st-century learning emphasize critical thinking, creativity, communication, collaboration, and digital literacy. The Think Talk Write (TTW) learning model is known to be effective in developing students' thinking and communication skills, but its implementation in elementary schools still faces obstacles, particularly the lack of engaging visual media and suboptimal technology integration. This study aims to describe how the use of Canva can transform the implementation of the TTW model to make it more relevant to the needs of 21st-century learning. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results show that the integration of Canva at each stage of the TTW model can make the learning process more visual, interactive, and collaborative. In the Think stage, Canva provides visual stimuli that strengthen the process of understanding information. In the Talk stage, digital collaboration features allow students to discuss and build ideas together. In the Write stage, students can compose text creatively with the support of various design elements. This study concludes that the use of Canva provides significant added value to the TTW model, making it more adaptive to digital literacy and 21st-century competencies.